Synthetic cannabinoids induced psychotic episode as differential diagnostic challenge: clinical case - Safonov, D. M.; Сафонов, Дмитро Миколайович (My University, 2019)
In order to highlight a problem of differential diagnostic of primal psychotic episode which induced by "smoking mixtures" intoxication, the case of a primary psychotic episode of schizophrenia due to the use of cannabinoids, which is primarily qualified as acute polymorphic psychotic disorder with symptoms of schizophrenia has been described. As a result, the issue of clinical differential diagnosis of the genesis of acute polymorphic psychotic disorder with symptoms of schizophrenia induced by synthetic cannabinoids was revealed.
Keywords: cannabinoids; smoking mixtures; primal psychotic episode